Agriculture and environmental sciences community portal [electronic resource] (MERLOT, 2017)
Quoted from the homepage: Welcome to the MERLOT Agriculture and Environmental Sciences Portal, an educational resource for teaching and learning. Use this portal to discover online learning materials, MERLOT members, journals, professional organizations, and news in your discipline. You are also invited to join MERLOT ? it's free! As a member of MERLOT, you can contribute to this growing community of instructors and students by using and rating the learning materials you find, submitting online learning materials for evaluation that you have created or that you have used. MERLOT prides itself on the peer reviews of material in our collection. As a member you can become a peer reviewer which has many benefits! The peer review process for evaluating the teaching and learning resources in MERLOT follows a standard model and is led by Editors and editorial boards. Faculty members are selected in accordance with MERLOT guidelines. For more information, email beareviewer@merlot.org or visit our Peer Review Information page.